EVALUATION OF THE AETIOLOGICAL SPECTRUM OF OBSTRUCTIVE JAUNDICE - Siddique, Khurram; Ali, Qasim; Mirza, Shirin; Jamil, Aiza; Ehsan, Aisha; Latif, Sarmad; Malik, Asif Zafar (Journal of Ayub Medical College Abbottabad, 2008)
Background: Jaundice is a common problem in medical and surgical gastroenterological practice. The surgical jaundice can be caused by the obstruction of the bile duct as with gall stones, strictures, malignancy, such as cholangiocarcinoma (in which the jaundice is persistent and progressive), periampullary carcinoma, carcinoma gall bladder 6 and carcinoma head of pancreas. The objective of this descriptive study was to evaluate the Etiological spectrum of obstructive jaundice. Methods: A prospective, descriptive study was carried out at Surgical Unit-II Holy family Hospital, Rawalpindi, from mid of May 2006 till March 2007. Sixty patients, who presented in the surgical OPD of Holy family Hospital, were included in the study. Thorough history and physical examination was followed by biochemical tests and various investigations like USG abdomen, ERCP, CT-Scan, & MRCP and histopathology. The data was analyzed using SPSS ver 14.0. Results: Of the 60 patients; 40 (66.66%) were male and 20 (33.33%) were female, their mean age being 49.50 years. Malignant obstructive jaundice was seen in 34 (56.66%) patients while 26 (43.33%) had benign etiology. Amongst the commonest symptom; clay coloured stools (75%) was more frequent in patients with malignant disease whereas abdominal pain (51.66%) was most common in benign conditions. Commonest malignancy was Carcinoma (Ca) of the head of pancreas 18/60 (30%) followed by Ca gall bladder 8/60 (13.33%), cholangiocarcinoma 7/60 (11.66%), and periampullary carcinoma 1/60 (1.66%). Choledocholithiasis 21/60 (35%) was the commonest benign cause followed by stricture of common bile duct 3/60 (5%) and acute pancreatitis 2/60 (3.33%). Conclusion: Obstructive jaundice is common amongst females and the cause is mostly malignant. Ca head of pancreas is the commonest malignancy while Choledocholithiasis is the commonest benign cause. USG, ERCP and CT-Scan are important diagnostic modalities for evaluation of patient with obstructive jaundice with ERCP having the additional advantage of being therapeutic as well. Keywords: Choledocholithiasis, Obstructive jaundice, ERCP, Ca Head of pancreas, Ca gall bladder.